Malondialdehyde in exhaled breath condensate and urine as a biomarker of air pollution induced oxidative stress - Gong, Jicheng (2013)
Underlying mechanisms by which air pollutants adversely affect human health remain poorly understood. Oxidative stress has been considered as a potential mechanism that may promote lipid peroxidation by reactive oxygen species, leading to the formation of malondialdehyde (MDA) that is excreted in biofluids (e.g., urine and exhaled breath condensate (EBC)). A panel study was conducted to examine whether concentrations of MDA in EBC and urine were associated, respectively, with changes in air pollution levels brought by the Beijing Olympic air pollution control measures. EBC and urine samples from 125 healthy adults were collected twice in each of the pre-, during-, and post-Olympic periods. Period-specific means of MDA and changes in MDA levels associated with increases in 24-h average pollutant concentrations were estimated using linear mixed-effects models. From the pre- to the during-Olympic period, when concentrations of most pollutants decreased, EBC MDA and urinary MDA significantly decreased by 24% (P < 0.0001) and 28% (P = 0.0002), respectively. From the during-Olympic to the post-Olympic period, when concentrations of most pollutants increased, EBC MDA and urinary MDA increased by 28% (P = 0.094) and 55% (P = 0.046), respectively. Furthermore, the largest increases in EBC MDA associated with one interquartile range (IQR) increases in all pollutants but ozone ranged from 10% (95% CI: 2%, 18%) to 19% (95% CI: 14%, 25%). The largest increases in urinary MDA associated with IQR increases in pollutant concentration ranged from 9% (95%: 0.3%, 19%) to 15% (95% CI: 3%, 28%). These findings support the utility of EBC MDA as a biomarker of oxidative stress in the respiratory tract and urinary MDA as a biomarker of systemic oxidative stress in relation to air pollution exposure in healthy young adults. Both EBC and urine samples can be collected noninvasively in the general population.